The use of activated partial thromboplastin time versus antifactor Xa assay in monitoring continuous unfractionated heparin infusion therapy in obstetric intensive care unit - Hany V. Zaki; Marwa A.K. Elbeialy; Ahmed M. Soliman (Ain Shams Journal of Anesthesiology, 2019)
Abstract Background Unfractionated heparin (UFH) infusion therapy needs accurate tight control to prevent overanticoagulation that may result in hemorrhagic complications and also to prevent sub therapeutic level that may result in thrombotic complications. The aim of this study was to compare the most popular monitoring tool activated aPTT versus antifactor Xa to reach accurate monitor to UFH therapy in critically ill pregnant females. Results Time to reach therapeutic level as well as total heparin dose required to reach this therapeutic level were much lower in the anti-Xa group when compared to aPTT group. Conclusion The use of anti-Xa-based protocol to monitor UFH infusion therapy resulted in better therapeutic control as it resulted in earlier achievement of therapeutic level and lower heparin dose requitments.